Eduardo Paolozzi and the lost realms of child art. (2019) - Williamson, Beth
Abstract : Throughout the 1940s and 1950s, and beginning with the inaugural National Exhibition of Children's Art in 1948, Eduardo Paolozzi was called upon to select children's artworks for display. Paolozzi not only saw child art as a legitimate point of reference, but children's creativity as a lost realm to be reclaimed by the artist. This article examines Paolozzi's making and teaching at the Central School of Arts and Crafts in London, alongside his engagement with contemporaneous thinking on child art and his relationship with two of its main protagonists – William Johnstone and Anton Ehrenzweig. Furthermore, focusing a pedagogical lens on Paolozzi's own sculpture at this time, this article will consider how an interest in child art plays out in those sculptural works. Ultimately, the question here is how Paolozzi's interest in child art at this time inflected his own artistic practice and pedagogy.